MOF derived porous carbon-Fe3O4 nanocomposite as a high performance, recyclable environmental superadsorbent - Banerjee, Abhik; Gokhale, Rohan; Bhatnagar, Sumit; Jog, Jyoti Prakash; Bhardwaj, Monika; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Materials Chemistry, 2012)
A high surface area carbon composite with Fe3O4 nanoparticles is synthesized by pyrolysis of an iron containing Metal Organic Framework (MOF). The composite can be prepared by annealing the MOF at different temperatures (500 degrees C and 600 degrees C), each case exhibiting unique properties in terms of the hydrophobic behaviour and surface area, resulting in specific applicability domains. We highlight the exceptional behaviour of this material as a magnetically separable and recyclable superadsorbent for removal and recovery of environmental pollutants (oil/hydrocarbon and dye/phenol).

MOF-derived crumpled-sheet-assembled perforated carbon cuboids as highly effective cathode active materials for ultra-high energy density Li-ion hybrid electrochemical capacitors (Li-HECs) - Banerjee, Abhik; Upadhyay, Kush Kumar; Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Nanoscale, 2014)
Lithium ion hybrid capacitors (Li-HECs) have attracted significant attention for use in next generation advanced energy storage technologies to satisfy the demand of both high power density as well as energy density. Herein we demonstrate the use of very high surface area 3D carbon cuboids synthesized from a metal-organic framework (MOF) as a cathode material with Li4Ti5O12 as the anode for high performance Li-HECs. The energy density of the cell is similar to 65 W h kg(-1) which is significantly higher than that achievable with commercially available activated carbon (similar to 36 W h kg(-1)) and a symmetric supercapacitor based on the same MOF-derived carbon (MOF-DC similar to 20 W h kg(-1)). The MOF-DC/Li4Ti5O12 Li-HEC assembly also shows good cyclic performance with similar to 82% of the initial value (similar to 25 W h kg(-1)) retained after 10 000 galvanostatic cycles under high rate cyclic conditions. This result clearly indicates that MOF-DC is a very promising candidate for future P-HEVs in a Li-HEC configuration.

Mitigating dendrite formation on a Zn electrode in aqueous zinc chloride by the competitive surface chemistry of an imidazole additive - Rana, Ashutosh; Thakare, Anup; Kumar, Nikhil; Mukherjee, Buddhadev; Torris, Arun; Das, Bidisa; Ogale, Satishchandra; Banerjee, Abhik (ACS Applied Materials and Interfaces, 2023)
Electrochemical energy storage systems are critical in several ways for a smooth transition from nonrenewable to renewable energy sources. Zn-based batteries are one of the promising alternatives to the existing state-of-the-art Li-ion battery technology, since Li-ion batteries pose significant drawbacks in terms of safety and cost-effectiveness. Zn (with a reduction potential of -0.76 V vs SHE) has a significantly higher theoretical volumetric capacity (5851 mAh/cm3) than Li (2061 mAh/cm3), and it is certainly far less expensive, safer, and more earth-abundant. The formation of dendrites, hydrogen evolution, and the formation of a ZnO passivation layer on the Zn anode are the primary challenges in the development and deployment of rechargeable zinc batteries. In this work, we examine the role of imidazole as an electrolyte additive in 2 M ZnCl2 to prevent dendrite formation during zinc electrodeposition via experimental (kinetics and imaging) and theoretical density functional theory (DFT) studies. To characterize the efficacy and to identify the appropriate concentration of imidazole, linear sweep voltammetry (LSV) and chronoamperometry (CA) are performed with in situ monitoring of the electrodeposited zinc. The addition of 0.025 wt % imidazole to 2 M ZnCl2 increases the cycle life of Zn-symmetric cells cycled at 1 mA/cm2 for 60 min of plating and stripping dramatically from 90 to 240 h. A higher value of the nucleation overpotential is noted in the presence of imidazole, which suggests that imidazole is adsorbed at a competitively faster rate on the surface of zinc, thereby suppressing the zinc electrodeposition kinetics and the formation. X-ray tomography reveals that a short circuit caused by dendrite formation is the main plausible failure mechanism of Zn symmetric cells. It is observed that the electrodeposition of zinc is more homogeneous in the presence of imidazole, and its presence in the electrolyte also inhibits the production of a passivating coating (ZnO) on the Zn surface, thereby preventing corrosion. DFT calculations conform well with the stated experimental observations.
Keywords: dendrite; Density functional theory; exchange current density; Imidazole; X-ray computed tomography; zinc metal electrodeposition